2019
DOI: 10.1111/nep.13545
|View full text |Cite
|
Sign up to set email alerts
|

Snap shot view on anaemia in chronic kidney disease of uncertain aetiology

Abstract: Aim Anaemia is a well‐known complication of chronic kidney disease but there are no published studies on the pattern of anaemia in chronic kidney disease of uncertain aetiology (CKDu). This study aims to find out the prevalence, causes and associations of anaemia in CKDu to identify any unique features which are different from already described anaemia in chronic kidney disease. Method All (119) biopsy‐confirmed CKDu patients in two endemic clinics (Girandurukotte and Wilgamuwa) were selected as cases. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…A recent study revealed that severity of CKDu is inversely associated with BMI and suggested that low BMI might increase susceptibility to the disease [59]. In the present study, we observed a higher prevalence of anemia among CKDu patients (70.8%), similar to previous findings (72.3%) [60].…”
Section: Discussionsupporting
confidence: 90%
“…A recent study revealed that severity of CKDu is inversely associated with BMI and suggested that low BMI might increase susceptibility to the disease [59]. In the present study, we observed a higher prevalence of anemia among CKDu patients (70.8%), similar to previous findings (72.3%) [60].…”
Section: Discussionsupporting
confidence: 90%
“… 8 Reliance on this histopathological label has led numerous researchers to describe their study subjects as including “biopsy-proven” CKDu patients. 40 , 41 , 42 , 43 , 44 This is potentially misleading. From a pathological point of view, the term tubulointerstitial nephritis (TIN), also referred to as interstitial nephritis, does not represent any specific disease entity and merely represents inflammation within the tubulointerstitium rather than in the glomerular and vascular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Fluoride (F - ) exposure via drinking water and its gradual accumulation in the body is nephrotoxic ( Fernando et al 2019a , 2019b , 2019c ; Nanayakkara et al 2020a , 2020b ; Perera et al 2020 ; Thammitiyagodage et al 2017 ). The synergistic influence of F - and water hardness can enhance CKDu (Balasooriya et al 2019 ; Wickramarathna et al 2017 ), particularly when high elevated levels of Mg 2+ contribute to water hardness (Dharmawardana 2017 ; Wickramarathna et al 2017 ).…”
Section: Main Textmentioning
confidence: 99%
“…Urine is considered an excellent source for biomarkers since markers resulting from the pathophysiological processes in the kidney are released into urine (Fernando et al 2019a , 2019b , 2019c ). Urinary KIM-1 (kidney injury molecule) is a good predictor for renal injury prior to detectable eGFR changes (Ichimura et al 1998 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation